Myocarditis and pericarditis after vaccination for COVID‐19 - Blake Hudson; Ryan Mantooth; Matthew DeLaney (Journal of the American College of Emergency Physicians Open)
Abstract Two previously healthy males presented to the emergency symptoms with signs of pericarditis/myocarditis after being vaccinated with an mRNA vaccine for COVID‐19.